The ways of restoration of effective scientific and technical activity as a constituent of innovative-investment development of Ukraine (Economics and region, 2019)
It is analysed scientific literature, which allowed selecting such interconnected concepts, as scientific and technical achievements, technological development, innovations, innovative-investment development. It is considered the problems of resuming scientific and technical activity as a constituent of innovative-investment development of Ukraine. The authors worked on the development of scientific and technical sphere of activity status and basic ways of its perfection. The scientists studied the experience of the developed countries in solution of the indicated problem. It is analysed financing of scientific and technical activity in Ukraine. It is underlined the importance of the personal interest of active investors, grants of state guarantees of providing of their financial interests. The authors indicated the necessity of substantial changes for the system of organization of scientific researches. It is proved the urgence of activation of efforts of state administration for forming the favourable investment climate in the country.
Keywords: scientific and technical achievements; technological development; innovations; innovative investment development